Implementation Of The Multi Objective Optimization Method On The Basis Of Ratio Analysis (Moora) In Determining The Procurement Of Goods At The General Bureau Of The Government Bengkulu Province - Nanda Pratama Putra; Yupianti Yupianti; Devi Sartika (Penerbit Jurnal Indonesia, 2023)
Procurement is an activity related to the fulfillment/provision of resources (goods or services) in a particular project organized by a company. Conventional procurement is considered to have several disadvantages, such as the ease of Corruption, Collusion, and Nepotism (KKN) to develop and lack of transparency. Conventional procurement also takes a long time so that it is seen as a waste of time and money, lack of information and unfair competition. Alternatives that can be done to solve procurement problems by using information technology Decision Support System (SPK) with the Multi-Objective Optimization on The Basic of Ratio Analysis (MOORA) method. The results of the tests that have been carried out obtained have ranked the companies that will be recommended to procure goods at the General Bureau of Bengkulu Province. The use of MOORA is able to analyze and provide recommendations in Goods activities.